Incidence of cancer among workers in a Norwegian nitrate fertiliser plant. Issue 7 (July 1993) - Fandrem, S I; Kjuus, H; Andersen, A; Amlie, E
Abstract : The incidence of cancer among 2023 male fertiliser workers has been investigated in a historical cohort study. Workers who had been employed for more than one year in work with possible exposure to dust containing nitrate between 1945 and 1979 were included. An individual cumulated exposure to dust expressed in level-years was calculated for each participant. The cohort was followed up from 1953 to the end of 1988, and the incidence of cancer was compared with the national rates. There were 467 deaths v 504.8 expected (standardised mortality ratio (SMR) = 0.93), and 185 cases of cancer v 195.5 expected (standardised incidence ratio (SIR) = 0.95). Thirty cases of lung cancer were found v 27.5 expected (SIR = 1.09). No overall excess of gastric cancer was found (15 cases v 17.0 expected; SIR = 0.89). No association was found between cumulated exposure to nitrate and gastric cancer, and there was no association between duration of employment or time since first employment and incidence of gastric cancer.